2014
DOI: 10.1155/2014/657851
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effects of Tai Chi, Resistance Training, and Diet on Physical Function and Body Composition in Obese Older Women

Abstract: Obesity is a major health problem in the USA, especially in minority populations over the age of 60 years, and the aging process can cause adverse effects on physical function. Previous research has shown that Tai Chi, resistance training (RT), and diet result in overall health improvements. However, the combination of these specific interventions has yet to be translated to obese older women in an urban setting. The purpose of this study was to examine a combined intervention on the primary outcomes of physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
1
11
0
2
Order By: Relevance
“…In general, studies have reported significant improvements in body composition, as indicated by significantly decreased fat mass and increased lean mass, [ 20 , 38 ] as well as muscle structural changes, [ 14 ] strength gain, [ 14 , 20 , 38 ] and functional mobility. [ 19 , 21 , 34 , 38 ] Our findings in elderly patients with sarcopenia or obesity are in concordance with those of previous studies on elastic resistance exercise in older adults.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In general, studies have reported significant improvements in body composition, as indicated by significantly decreased fat mass and increased lean mass, [ 20 , 38 ] as well as muscle structural changes, [ 14 ] strength gain, [ 14 , 20 , 38 ] and functional mobility. [ 19 , 21 , 34 , 38 ] Our findings in elderly patients with sarcopenia or obesity are in concordance with those of previous studies on elastic resistance exercise in older adults.…”
Section: Discussionsupporting
confidence: 92%
“…Elastic band RET has been recently used for elderly individuals who are obese [ 20 , 21 , 38 ] or not obese. [ 14 , 19 , 34 , 52 ] Overall, these studies have used exercise protocols with an intervention period of 8 to 24 weeks, a frequency of 2 to 5 times per week, and a low to moderate exercise intensity level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, relevant studies have used exercise protocols with an intervention period of 8–24 weeks, a frequency of 2–5 times per week, and a low to moderate-intensity. In general, studies have reported that body composition is improved through significant reductions in fat mass and increases in lean mass 33 , 35 , which also positively affect muscle structural change 18 , strength gain 18 , 22 , 33 , 35 , 39 , and functional mobility 24 , 33 , 34 , 36 39 . The results of relevant studies on elastic resistance exercise in elderly people support our findings concerning older individuals with sarcopenic obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Tai Chi is a spiritual art that focuses on slow and fluid movements through a full range of motion focusing on balance, core strength, flexibility, and meditation techniques (24). Tai Chi is known for its beneficial effects on blood pressure when combined with other forms of lifestyle modifications (6, 16). However, the most frequently prescribed exercise for cardiovascular benefits is walking for 150 minutes per week (7).…”
Section: Introductionmentioning
confidence: 99%